Oxidant‐Resistant Hydrogen‐Bond‐Donating Organocatalyst for Enantioselective Nucleophilic Epoxidation of α, β‐Unsaturated Amides. Issue 4 (24th March 2014) - Kobayashi, Yusuke; Li, Shanji; Takemoto, Yoshiji
Abstract Bifunctional benzothiadiazine‐catalyzed epoxidation of α, β‐unsaturated amides proceeds efficiently to give chiral 2‐oxiranecarboxamides in excellent yields of 89–99 % and with good enantioselectivity of up to 84 % ee. A synthetic application of the oxiranecarboxamides is also described.